Penyuluhan Media Leaflet dan Video Animasi Tentang Pentingnya Kesehatan Gigi Mulut Pengunaan dan Pembuatan Gigi Tiruan pada Siswa-Siswi dan Guru - Didik Marsigid; Imas Maesaroh; Tasrip Tasrip (Publikasi Indonesia, 2022)
The use of dentures as a substitute for missing teeth is very important, but not everyone with missing teeth wears dentures. Dental and oral health education is an effort to convey messages about dental and oral health. Dental and oral health education requires facilities in the form of educational media, because it can facilitate the delivery of information. Students and teachers at the Assa'adah Orphan Islamic Boarding School in the Kebayoran Baru area, South Jakarta are the right target considering that orphaned and dhuafa adolescents are teenagers from a disadvantaged economic class and are in their infancy who need maintenance of dental health and prevention of tooth decay and repair if you have lost your teeth by making dentures so that they can improve masticatory and aesthetic functions. The purpose of this community service is to improve masticatory and aesthetic functions for SMPI Students and Teachers of the Orphan Islamic Boarding School Assa'adah Jakarta The method of implementing this community service is carried out by conducting counseling with animated video media and leaflet media about the importance of oral health in the use and manufacture of dentures. This activity was attended by 110 students consisting of 55 counseling students on video media methods and 55 students on leaflet media counseling. The results achieved were an increase in knowledge before and after counseling with animated video media with a pre-test score of 387 post test 518 an average score of 9.42 for Leaflet media has a pre-test score of 358, posttest has an average score of 8.1. The conclusion is that there are differences in the knowledge of the post-test group and the animated video media group and the leaflet media with the results of the Independent Sample T-Test different test, it is obtained that the value of Sig.(2-tailed) ) of 0.000 <0.05.